Professional training improves early education teachers’ knowledge, skills, motivation, and self-efficacy - Hyseni Duraku, Zamira; Blakaj, Vigan; Shllaku Likaj, Eglantina; Boci, Loreta; Shtylla, Hysnie (Frontiers in Education, 2022)
This study aimed to evaluate the impact of a training program for professional development on early education teachers’ knowledge and skills, work motivation, and self-efficacy. A one-group pre–post-test design was used to assess the effect of the training program on 75 teachers working in public early education institutions in the Tirana municipality in Albania. The results indicated that completing training was associated with a significant increase in early education teachers’ knowledge and skills, work motivation, and self-efficacy. These findings demonstrate the multiple benefits of professional training as a mechanism for supporting teachers’ personal and professional development and improving teaching practice, the quality of early education settings, and children’s early learning and growth experiences. Implications for practice, study limitations, and future research directions are also discussed.